A new substitute name for Bidessus (Bidessodes) plicatus Zimmermann, 1921 (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) - Hájek, Jiří (Zootaxa, 2012)
During a study of the World catalogue of Dytiscidae (Nilsson 2001) I found an overlooked primary homonymy in the genus Bidessus Sharp, 1882 (Hydroporinae: Bidessini). Bidessus (Bidessodes) plicatus Zimmermann, 1921 (currently in the genus Bidessodes Régimbart, 1900) from Brazil is preoccupied by Bidessus plicatus Sharp, 1882 (currently in the genus Liodessus Guignot, 1939) from New Zealand. As the identity of both taxa is clear, I propose a new substitute name for the junior homonym.